When Spatial Dimension Matters: Comparing Personal Network Characteristics in Different Segregated Areas - Huszti, Éva (Social Inclusion, 2021)
Living in segregated areas with concentrated neighbourhood poverty negatively affects the quality of life, including the availability of local jobs, access to services, and supportive social relationships. However, even with similar neighbourhood poverty levels, the degree and structure of spatial separation vary markedly between such areas. We expected that the level of spatial segregation aggravates the social exclusion of its inhabitants by negatively affecting their social capital. To test this hypothesis, we identified three low‐income neighbourhoods with high poverty rates (78%) in a medium‐sized town in Hungary, with different levels of integration in the city (based on characteristics such as the degree of spatial separation, infrastructure, and availability of services). The three neighbourhoods were located in two areas of differing degrees of integration in the fabric of the city: fully integrated, semi‐integrated (integrated into the surrounding residential area but isolated from the city), and non‐integrated. 69% of the 394 households in these areas were represented in our sample (one respondent per household). We interviewed respondents regarding the size and composition of their personal networks. Our results, which also distinguished between Roma and non‐Roma inhabitants, showed that those living in the spatially more integrated area not only have the largest and most diverse networks but seem to have a strong, "bonding‐based" cohesive community network as well. Even the non‐Roma who live there have ethnically heterogeneous—in other words—Roma network members. The disintegrated area, on the other hand, is characterised by both spatial and social isolation.